Analyses of the development and challenges of parkour coaches’ education in Europe - Kolar, Edvard (Annales kinesiologiae (Koper), 2025)
Purpose: Parkour historically developed as an urban community “lifestyle” move-ment that relied mainly on informal teaching and training methodologies. With formal institutionalization, parkour has transitioned into more formalized structures, includ-ing established training academies, coaching certifications, and competitive events. This article presents a structured literature review with the aim of providing an over-view of the historical, philosophical/ideological, organizational/institutional, and edu-cational aspects of parkour coach education and knowledge development in Europe. Based on the review, key challenges for future development are also highlighted.Method: For the purposes of a structured literature review, the search and selection process followed the general principles of the PRISMA 2020 statement as a framework, rather than a formal systematic review protocol. Google Scholar was chosen as the pri-mary search platform. Following the initial screening and analysis, 12 relevant sources were included in the in-depth review. In addition to the literature review, online sources from professional international sports organizations involved in education, training, and certification of parkour coaches were also examined. Findings: It can be noted that parkour in Europe is still predominantly developed and understood as a “lifestyle” urban activity with the gradual parallel formation of an institutional, formal sports discipline, which is reflected in the intra-organizational and philosophical-ideological conflict between participants and (opinion) leaders of parkour. These conflicts are also evident at the level of training/education of parkour coaches and instructors.Conclusions: Recognizing and respecting parkour’s roots as a self-organized cul-ture is essential if institutionalization is to enhance rather than diminish the discipline’s diversity, creativity, and authenticity.
Keywords: coaches; education; formalizacija; formalization; institucionalizacija; institutionalization; parkour; sport; šport; training; trenerji; usposabljanje